Validity Concerns for Counsellors Using the 1978 Edition of the Career Maturity Inventory - Chodzinski, Raymond T. (Canadian Journal of Counselling and Psychotherapy, 2011)
Validity of the Career Maturity Inventory (CMI) was investigated using 279 grade ten and 256 grade twelve students. Factor analysis of the ten subtests of the CMI and the regression of the CMI variables on intelligence scores, sex, and grade indicated partial support of the theoretical postulations. Two principal factors emerged, but the CMI Competence and Attitude subtests did not load distinctly on the separate factors. As expected, intelligence, grade, and sex were found to be significant predictors of the CMI variables. However, evidence for discriminant validity was unsatisfactory and inconsistent with the theoretical framework of CMI. Implications for theory and practice are discussed.